Peran Tabungan dalam Menghimpun Dana Pihak Ketiga Pada Bank Sumut Kcp. Syariah Simpang Kayu Besar - Yusuf Yusuf; Nurul Jannah (Yayasan Rahmat Islamiyah, 2021)
The development of banking in Indonesia is currently relatively stable and continues to grow, this study aims to determine the role of savings in raising third party funds at Bank Sumut Syariah KCP Simpang Kayu Besar. The research method used in this research is qualitative research with descriptive analysis technique. The source of the data in this research is that the primary data is interviewed with the bank and the secondary data in this study is a literature study. The bank usually collects third party funds from the public, namely by using the bank's own products consisting of demand deposits, savings and time deposits. At PT. Bank Sumut Syariah KCP Simpang Kayu Besar DPK was very high on deposit products in 2019, during the Covid-19 pandemic, deposits were not very helpful in increasing the bank's DPK. Savings have an important role in increasing third party funds at Bank Sumut Syariah KCP Simpang Kayu Besar.